EVALUATING STUDENT ENGAGEMENT AND COMPREHENSION IN DIVERSE ONLINE LEARNING ENVIRONMENTS IN CROSS RIVER STATE, NIGERIA (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
The rapid adoption of online learning in Nigeria has highlighted disparities in educational access and outcomes. This study evaluates student engagement and comprehension in online learning environments across urban and rural secondary schools in Cross River State, Nigeria, aiming to identify barriers and propose solutions for equitable education. Grounded in connectivism a theory emphasizing networked learning through digital connections the research investigates how technological and pedagogical factors influence learning outcomes in a context marked by socioeconomic and infrastructural variability. A quantitative research design was employed, utilizing primary data collected via structured surveys from 250 students and 60 teachers in 10 schools, selected through stratified random sampling to reflect urban (Calabar) and rural (Obudu, Yakurr) diversity. The method included Likert-scale questions and descriptive statistical analysis to measure engagement and comprehension metrics. Findings reveal an average engagement rate of 62% (mean 3.1) and comprehension of 58% (mean 2.9), with urban students outperforming rural peers (70% vs. 54% engagement; 65% vs. 48% comprehension). Key barriers include poor internet connectivity (68%), limited device access (52%), and inadequate teacher ICT skills (60%), disproportionately affecting rural areas. The study concludes that while online learning is feasible, its efficacy is curtailed by infrastructure and training deficits, widening the digital divide. Recommendations include government investment in broadband expansion, teacher ICT training, and device subsidies to enhance engagement and comprehension, ensuring inclusive education in Cross River State.